The Digital Frontier: Are There Online Courses for Healthcare AI? - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2022)
The Digital Frontier: Are There Online Courses for Healthcare AI? The integration of Artificial Intelligence (AI) into healthcare is no longer a futuris...
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation; Patient Care